ROLE OF INFORMATION TECHNOLOGY IN IMPROVING THE EFFICIENCE OF THE NATIONAL ADMINISTRATION - Cahyaning Bhakti Utami; Lilik Puja Rahayu, Heny Fajriyah Noviantika (ADMIN: Jurnal Administrasi Negara, 2024)
The study aims to analyze the role of information technology in improving the efficiency of state administration. The research method used is the study of literature, where sources of information such as articles, journals, books, and publications related to the subject are analyzed and synthesized. Research results show that information technology has a positive impact in improving state administration processes, through automation, business process simplification, improved accessibility, efficient data management, and better interdepartmental collaboration.